Environmental durability of vinyl ester composites filled with carbonized jatropha seed shell - N. A., Sri Aprilia; Hossain, Md. Sohrab; Abdullah, C. K.; Abdul Khalil, H. P. Shawkataly; Enih, Rosamah; Dungani, Rudi; Davoudpour, Yalda; Sarker, Md. Zaidul Islam (North Carolina State University * College of Natural Resources, 2015)

(untitled)
The durability of vinyl ester composites filled with carbonized jatropha seed shell was investigated in 5% NaOH solution, 5% HCl solution, and distilled water for 12 months. The environmental durability of the composites was determined by measuring weight changes, flexural properties, and tensile properties. Results showed weight gain and changes in the mechanical properties of the composites due to the soaking time in alkaline, acidic, and neutral environments. It was observed that vinyl ester composites had the highest tensile properties in alkaline environments. The highest flexural properties of the vinyl ester composites were observed in an alkaline environment. Scanning electron microscope image analysis revealed that the surface of the vinyl ester composites was rough and that the original luster was lost after soaking in alkaline solution, acidic solution, and distilled water for 12 months.